Harmonizing Halal in ASEAN: Analysis of Halal Food Guidelines under the ASEAN Way Approach - Eva Johan; Maria Jose Plana-Casado (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The research examined how ASEAN is moving towards legislative harmonization in the key economic sector of halal foods. The research investigated how ASEAN has promoted economic integration by building regional consensus regarding controversial issues, such as the definition of halal food, and discuss the role of other international instruments in building regional consensus – the “ASEAN” way. Qualitative methodology was used by integrating a historical, doctrinal, and comparative approach. The first analysis was on the process leading to adopting ASEAN halal food guidelines, which constitute the most concrete output of regional efforts to bring domestic standards closer. The following procedures were to compare and contrast these instruments substantively to identify the areas where new consensus has been found and those where disagreements persist. Finally, the research examined the potential influence of the guidelines adopted by the Codex Alimentarius Commission, the Organization of Islamic Cooperation, and MABIMS in drafting ASEAN instruments. The research concludes that despite of lengthy and difficult road to gaining consensus through the ASEAN way mechanism, member states have successfully agreed on some elements of halal standards. However, the guidelines require member states’ legislation to achieve full harmonization in addition to ASEAN soft law. Moreover, international initiatives have impacted ASEAN’s halal standards in important ways. Some issues regarding harmonization remain, such as mutual recognition and labelling, and require further investigation.